Unveiling the Antifungal Potential of Two Iberian Thyme Essential Oils: Effect on C. albicans Germ Tube and Preformed Biofilms - Alves, Melissa; Gonçalves, Maria José; Zuzarte, Mónica; Alves-Silva, Jorge M.; Cavaleiro, Carlos; Cruz, Maria Teresa; Salgueiro, Lígia (Frontiers in Pharmacology, 2019)
Fungal infections remain a burden worldwide, thus underpinning the need for effective new therapeutic approaches. In the present study, the antifungal effect of the essential oils of two thyme species, Thymus camphoratus and T. carnosus, used in traditional medicine in Portugal, as well as their major compounds was assessed. A special focus was placed on their effect on Candida albicans virulence factors. Also, the safety profile of the essential oils was assessed on keratinocytes. The essential oils were analyzed by gas chromatography and mass spectrometry. The minimal inhibitory and minimal fungicidal concentrations of the essential oils and their main compounds were assessed on reference and clinical strains. Also, their effect on C. albicans germ tube formation, metabolism and biofilm disruption were considered. T. camphoratus oil was rich in 1,8-cineole and α-pinene whereas T. carnosus oil showed high amounts of borneol and camphene. Regarding the antifungal effect, both oils were more active against Cryptococcus neoformans and dermatophytes and very effective in inhibiting C. albicans germ tube formation, at doses well below their MIC and in a higher extend than the isolated compounds and fluconazole, an antifungal drug widely used in the clinic. The oils also disrupted preformed C. albicans biofilms. Furthermore, no toxicity was observed at pharmacological relevant concentrations towards keratinocytes. Our study validates the traditional uses ascribed to these Iberian species. Furthermore, it brings new insights on the antifungal potential and mechanism of action of these thyme species, thus paving the way for the development of novel effective antifungal drugs.